2018
DOI: 10.3389/fpsyg.2018.01544
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Risk and School Readiness: Longitudinal Mediation Through Children's Social Competence and Executive Function

Abstract: The association of socioeconomic status with academic readiness and school achievement is well established. However, the specific contributions of cognitive and social aspects of self-regulation, and potential reciprocal relations between them in the prediction of school readiness and early school achievement have not previously been examined. This study examined mediational processes involving children's executive function (EF) skills at 58 months and Grade 1 (G1) and social competence in Kindergarten (K) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 98 publications
(130 reference statements)
5
26
0
1
Order By: Relevance
“…We found that negative caregiving in infancy independently predicted a child’s ADHD symptom severity across childhood, and SES-risk predicted inattention symptom severity across childhood, but not hyperactivity/impulsivity symptoms. Our findings are supported by animal studies showing that adverse environmental conditions and reprogramming of HPA axis impact the development of the mesocortical and mesolimbic DA system in limbic regions and the PFC ( Tost et al, 2015 ), and by human studies reporting that exposure to early adversity during the first years of life elevates the likelihood of poor neurobehavioral development, impairs attention and self-regulation skills, and increases the risk for mental disorders ( Yoshikawa et al, 2012 ; Blair and Raver, 2016 ; Perry et al, 2018 ).…”
Section: Discussionsupporting
confidence: 79%
“…We found that negative caregiving in infancy independently predicted a child’s ADHD symptom severity across childhood, and SES-risk predicted inattention symptom severity across childhood, but not hyperactivity/impulsivity symptoms. Our findings are supported by animal studies showing that adverse environmental conditions and reprogramming of HPA axis impact the development of the mesocortical and mesolimbic DA system in limbic regions and the PFC ( Tost et al, 2015 ), and by human studies reporting that exposure to early adversity during the first years of life elevates the likelihood of poor neurobehavioral development, impairs attention and self-regulation skills, and increases the risk for mental disorders ( Yoshikawa et al, 2012 ; Blair and Raver, 2016 ; Perry et al, 2018 ).…”
Section: Discussionsupporting
confidence: 79%
“…The attainment of appropriate social skills through social interactions with peers (in addition to caregivers) may be an important driving component of EF development. In line with this idea, we recently reported findings of a novel developmental pathway whereby social competence through EF longitudinally mediated the impact of cumulative poverty-related adversities on academic achievement across the early school years (Perry et al, 2018a). Specifically, social competence in Kindergarten through EFs at Grade 1 longitudinally mediated a negative association between early-life poverty-related cumulative risk exposure and academic skills at Grade 2.…”
Section: Introductionmentioning
confidence: 68%
“…Thus, it is plausible that scarcity–adversity induced differences in working memory might co-occur with problems related to inhibitory control and cognitive flexibility. However, working memory, inhibitory control, and cognitive flexibility differ in their developmental trajectories, and are subserved by overlapping but unique neural networks (for review see Perry et al, 2018a) which could be differentially impacted by scarcity–adversity. Thus, it is also plausible that scarcity–adversity might uniquely impact the development of each core EF based on the developmental timing of adversity exposure and/or the mechanisms by which adversity influences the developing brain areas underlying EF development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations